Gwendy's final task - King, Stephen, 1947-; Chizmar, Richard, 1965- (King, Stephen, 1947- Gwendy's button box, 2022)
"When Gwendy Peterson was twelve, a mysterious stranger named Richard Farris gave her a mysterious box for safekeeping. It offered treats and vintage coins, but it was dangerous. Pushing any of its seven colored buttons promised death and destruction. Years later, the button box entered Gwendy's life again. A successful novelist and a rising political star, she was once again forced to deal with the temptation that box represented. Now, evil forces seek to possess the button box and it is up to Senator Gwendy Peterson to keep it from them. At all costs. But where can you hide something from such powerful entities? In Gwendy's Final Task, "horror giants" (Publishers Weekly) Stephen King and Richard Chizmar take us on a journey from Castle Rock to another famous cursed Maine city to the MF-1 space station, where Gwendy must execute a secret mission to save the world. And, maybe, all worlds."--provided by publisher.